Assignment Artifacts and What They Reveal About How Occupation Is Addressed in U.S. Occupational Therapy Curricula. - Hooper, Barb; Krishnagiri, Sheama; Price, Pollie; Taff, Steven D.; Bilics, Andrea (American Journal of Occupational Therapy)
Importance: Artifacts convey essential skills, tools, and concepts to students. Studies of artifacts can therefore illumine priorities for learning. Objective: To describe the skills, tools, and concepts that assignment artifacts required students to learn, especially in relation to occupation. Design: Educators submitted 243 artifacts that illustrated how their programs addressed occupation. Artifacts included syllabi, lectures, assignments, rubrics, study guides, texts, and learning objectives. A sociocultural research paradigm informed a secondary analysis of all assignment artifacts. Assignments were coded for the skills, tools, and underlying concepts students were to use, particularly related to occupation. Setting: U.S. occupational therapist and occupational therapy assistant academic programs. Participants: Twenty-five U.S academic programs selected through stratified random sampling that targeted representation by geographic region and the Carnegie Classification of Institutions of Higher Education. Fifteen occupational therapy and 10 occupational therapy assistant programs consented. Results: Assignment artifacts required students to interview, observe, analyze, and teach (skills); artifacts emphasized learning the Occupational Therapy Practice Framework: Domain and Process (tool). Few artifacts required students to relate skills and tools to broader concepts, including occupation. Those that did used prompts that were ancillary to the assignment. Grading rubrics seldom measured students' ability to connect skills and tools to occupation. Conclusions and Relevance: By emphasizing skills and tools detached from the concepts supporting their relevance to occupation, the artifacts reflected black box learning. Creating artifacts that reflect glass box learning can improve education. In glass box learning, artifacts are transparent and clearly delineate the skills, tools, and conceptual understandings to be gained. What This Study Adds: For researchers, the study highlights the importance of including artifacts in studies of occupational therapy education. For educators, the study gives guidance for creating assignments that clearly delineate skills, tools, and concepts.